2020
DOI: 10.5114/reum.2020.99995
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in systemic sclerosis therapy

Abstract: Systemic sclerosis (SSc) is a rare autoimmune disorder with a high mortality rate. There are still many unknowns concerning the pathophysiology of this disease, due to its clinical heterogeneity. Since there is still no curative treatment, researchers focus on finding novel methods to help the patients. One of the valid options is cellular therapy, and mesenchymal stem cells (MSCs)-based therapy yields great expectations. These cells possess especially valuable attributes regarding key points of SSc. Neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Numerous studies reported the beneficial effects of using MSCs in the treatment of cartilage ( Ma et al, 2018 ), graft-versus-host disease ( Zhao et al, 2019 ), ischemia ( Oliva, 2019 ), myocardial infarction ( Luo et al, 2017 ), and sclerosis ( Dudek et al, 2020 ). In this study, osteoblast and chondrocyte cell sheets were engineered, which can be harvested and transplanted in the required areas ( Tuan et al, 2013 ; Richardson et al, 2016 ; Oryan et al, 2017 ; Yorukoglu et al, 2017 ; Abdel Meguid et al, 2018 ; Egido-Moreno et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies reported the beneficial effects of using MSCs in the treatment of cartilage ( Ma et al, 2018 ), graft-versus-host disease ( Zhao et al, 2019 ), ischemia ( Oliva, 2019 ), myocardial infarction ( Luo et al, 2017 ), and sclerosis ( Dudek et al, 2020 ). In this study, osteoblast and chondrocyte cell sheets were engineered, which can be harvested and transplanted in the required areas ( Tuan et al, 2013 ; Richardson et al, 2016 ; Oryan et al, 2017 ; Yorukoglu et al, 2017 ; Abdel Meguid et al, 2018 ; Egido-Moreno et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%